Muškilāt Muwaṭṭa' Mālik Ibn-Anas - Baṭalyausī, ʿAbdallāh Ibn-Muḥammad al- 1052-1127 (Dār Ibn-Ḥazm, 1999)
Commentaries on Mālik ibn Anas, d. 795's Muwaṭṭaʼ; Islamic law; Malikites; early works to 1800.